"Give me mine angle": fishing for a moral in Antony and Cleopatra. (2nd January 2016) - Gurney, Evan
Abstract : This essay, which focuses on Shakespeare's Antony and Cleopatra, takes as its starting point an early scene in which Cleopatra calls for her angling rod and imagines herself fishing, an episode which has been used to illustrate the queen's mercenary hedonism. Building on recent scholarship that underscores the play's fundamental ambivalence, this article reads Antony and Cleopatra through the lens of the angler, or fisherman, a complex literary figure associated with seductive temptation and devilish deceit as well as apostolic cunning and ministerial accommodation, and in either case bound up in questions concerning the roles of rhetorical deception and theatrical spectacle. By associating Cleopatra with such a complicated figure, Shakespeare offers his own baited hook, dramatizing for his audience the perilous limitations and consequences of their own interpretive commitments.